Upaya Peningkatan Kualitas Sanitasi Masyarakat Pesisir Laut di Pulau Belakang Padang Menggunakan Communal Septic Tank - Irlas Helen Pakpahan; Amanatullah Savitri (Jurnal Manajemen Teknologi & Teknik Sipil, 2022)
Sanitation issues are important to pay attention to because they have a negative impact on various aspects of life. Development of sanitation facilities and infrastructure really needs efforts related to environmental aspects and public health. The problem that occurs in Kampung Tengah is about the quality of sanitation. The purpose of this research is to analyze sanitation problems that occur in Kampung Tengah village. From these data results will be obtained which will be used to improve and propose solutions for infrastructure development to improve sanitation conditions according to local conditions. Data collection used field observation methods by distributing data questionnaires. Then the data was tested using SPSS software, to ensure the validity and reliability of the data collected. The results showed that the sanitation quality of Kampung Tengah was classified as poor. Residents do not have a septic tank, the environment around the house is dirty and slum due to the absence of high tide. So it is necessary to improve the quality of sanitation by building a septic tank. The communal septic tank is a solution for the residents of Kampung Tengah who have limited land and cannot afford to build their own septic tank. In addition, to adapt to the socio-economic conditions of the residents, biofilter septic tank technology is needed. To meet the needs of the residents of Kampung Tengah, so sanitation can be improved.